Ki Hajar Dewantara's Critique of the 2022 Sisdiknas Bill: Implications for Islamic Education in Indonesia - Ode Rizki Prabtama; Ganang Dwi Kartika (Universitas Muhammadiyah Malang, 2024)
This research is a critical text study of the Philosophical Foundations contained in the Academic Text of the National Education System Draft Law (Sisdiknas Bill) which was socialized in August 2022. This philosophical study was carried out considering that the text of the Philosophical Foundations has fundamental weaknesses in it when viewed from a logical perspective. as well as Islamic spirituality, and Ki Hajar Dewantara's educational views as the founder of the educational philosophy in Indonesia with a religious and humanist character. This study aimed to explore Ki Hadjar’s thought as critics on Sisdiknas Bill and its implication of Islamic Education in Indonesia. The research questions are twofold. Firstly, what are the basic errors contained in the 'Philosophical Foundations' of the academic text of the 2022’s National Education System Bill. Secondly, what are the implications of the critics toward Islamic education in Indonesia. By using Bernadib's language philosophical method, the fundamental problems found in the 'Philosophical Foundations' text in the academic text of the 2022 National Education System Bill are uncovered. The analysis is then continued with the formulation of implications for Islamic education in Indonesia which is of concern to the majority of the Indonesia Muslim population. This research concludes there are crucial philosophical problems in 2022’s Sisdiknas Bill that could be in conflict with Islamic Education in Indonesia.